Hubungan Pola Asuh dan Budaya Pengasuhan terhadap deteksi dini pencegahan stunting pada Balita - Januarti, Luluk Fauziyah; Yulianto, Sofi; soliha, soliha (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Less than optimal parenting has a greater chance of stunting children. One of the causes of the high stunting rate in Bangkalan Regency is the lack of public knowledge and awareness about various matters concerning child growth and development and the culture of parenting that has been passed down from generation to generation. The factor of poor parenting in the family is one of the causes of the problem of nutritional intake needs. Parenting in the family includes several things such as breastfeeding intake, complementary foods, psychosocial stimulation, hygiene practices and environmental sanitation, care for children in a sick state. This study aims to analyze the relationship between parenting style and parenting culture on early detection of stunting in toddlers in Kab, Bangkalan. The research design in this study is analytical observation, with a Cross Sectional approach. Data collection using questionnaires with a sample of 70 respondents. The results of the study found that there is a relationship between parenting style and parenting culture to the incidence of stunting in toddlers.